Aripiprazole Improves Associated Comorbid Conditions in Addition to Tics in Adult Patients with Gilles de la Tourette Syndrome - Gerasch, Sarah; Kanaan, Ahmad Seif; Jakubovski, Ewgeni; Müller-Vahl, Kirsten R. (Frontiers in Neuroscience, 2016)
Gilles de la Tourette Syndrome (GTS) is characterized by motor and vocal tics, as well as associated comorbid conditions including obsessive-compulsive disorder (OCD), attention deficit/hyperactivity disorder (ADHD), depression, and anxiety which are present in a substantial number of patients. Although randomized controlled trials including a large number of patients are still missing, aripiprazole is currently considered as a first choice drug for the treatment of tics. The aim of this study was to further investigate efficacy and safety of aripiprazole in a group of drug-free, adult patients. Specifically, we investigated the influence of aripiprazole on tic severity, comorbidities, premonitory urge (PU), and quality of life (QoL). Moreover we were interested in the factors that influence a patient’s decision in electing for-or against- pharmacological treatment. In this prospective uncontrolled open-label study, we included 44 patients and used a number of rating scales to assess tic severity, PU, comorbidities, and QoL at baseline and during treatment with aripiprazole. 18 out of 44 patients decided for undergoing treatment for their tics with aripiprazole and completed follow-up assessments after 4-6 weeks. Our major findings were (1) aripiprazole resulted in significant reduction of tics, but did not affect PU; (2) aripiprazole significantly improved OCD and showed a trend towards improvement of other comorbidities including depression, anxiety and ADHD; (3) neither severity of tics, nor PU or QoL influenced patients’ decisions for or against treatment of tics with aripiprazole; instead patients with comorbid OCD tended to decide in favor of, while patients with comorbid ADHD tended to decide against tic treatment; (4) most frequently reported adverse effects were sleeping problems; (5) patients’ QoL was mostly impaired by comorbid depression. Our results suggest that aripiprazole may improve associated comorbid conditions in addition to tics in patients with GTS. It can be hypothesized that these beneficial effects are related to aripiprazole’s adaptive pharmacological profile, which exhibits an influence on the dopaminergic as well as a number of other neurotransmitter systems. For the first time, our data provide evidence that patients’ decision making process for or against medical treatment is influenced by other factors than tic severity and QoL.